1996
DOI: 10.1007/bf02254941
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome complement, C-banding, Ag-NOR and replication banding in the zebrafishDanio reio

Abstract: The chromosome complement of Danio rerio was investigated by Giemsa staining and C-banding, Ag-NORs and replication banding. The diploid number of this species is 2n = 50 and the arm number (NF) = 100. Constitutive heterochromatin was located at the centromeric position of all chromosome pairs. Nucleolus organizer regions appeared in the terminal position of the long arms of chromosomes 1, 2 and 8. Replication banding pattern allowed the identification of each chromosome pair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 13 publications
5
46
0
Order By: Relevance
“…S2). The long arm of Chromosome 4 was late replicating in 28 hpf embryos, which is consistent with previously published cytological data (Daga et al 1996;Sola and Gornung 2001;Anderson et al 2012). To further validate our results, an independent experimental replicate of 28 hpf embryos was generated.…”
Section: Resultssupporting
confidence: 91%
“…S2). The long arm of Chromosome 4 was late replicating in 28 hpf embryos, which is consistent with previously published cytological data (Daga et al 1996;Sola and Gornung 2001;Anderson et al 2012). To further validate our results, an independent experimental replicate of 28 hpf embryos was generated.…”
Section: Resultssupporting
confidence: 91%
“…Cytogeneticists numbered zebrafish chromosomes based on physical length (Pijnacker and Ferwerda 1995;Daga et al 1996;Gornung et al 1997Gornung et al , 2000Amores and Postlethwait 1999;Sola and Gornung 2001), so zebrafish genetic linkage group number and cytogenetic chromosome number are generally not the same. We assigned genetic linkage groups to physical chromosomes by fluorescent in situ hybridization (Phillips et al 2006), which showed that, for example, cytogenetic chromosome 3 is linkage group 4, called chromosome 4 in the reference genome and Chr4 in this work.…”
Section: Rad-tag Genotypingmentioning
confidence: 99%
“…Zebrafish does not, however, have a typical environmental sex-determination (ESD) mechanism like some sauropsids for which temperature is a cue (Charnier 1966;Lang and Andrews 1994;Merchant-Larios and Diaz-Hernandez 2013;Mork et al 2014). It is more probable that zebrafish is like medaka (Oryzias latipes) in having a genetic sex-determination mechanism that is sensitive to environmental conditions (Hattori et al 2007; Sato et al 2005;Selim et al 2009;Hayashi et al 2010).Zebrafish not only lacks classic ESD, but most stocks investigated do not have cytogenetically detectable chromosomal sex determination (Schreeb et al 1993;Pijnacker and Ferwerda 1995;Daga et al 1996;Gornung et al 1997;Amores and Postlethwait 1999;Gornung et al 2000;Sola and Gornung 2001;Traut and Winking 2001;Phillips et al 2006). In contrast, the only investigation of zebrafish taken directly from nature in India concluded that zebrafish females are the heterogametic sex (Sharma et al 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations